Effects of hemianesthesia hemineglect, and hemianopsia with disability score in patients with brain infarction - Ghandehari K; Ghandehari Z (مجله دانشگاه علوم پزشکی گرگان, 2007)
Background&Objective: Clinical findings effective on disability of stroke patients have importance due to their effects on prognosis and future recovery following rehabilitation. Materials&Methods: Consecutive stroke patients admitted in Valie-Asr hospital, Khorasan enrolled in a prospective study in 2005. Hemihyposthesia, hemianesthesia, hemineglect and homonymous hemianopsia were evaluated in the patients. Disability score was determined based on the Rankin scale at 72 hours post stroke. Mean of Rankin Disability Score (MRDS) was analysed by T and Fisher tests and p<0.05 declared as significant. Results: 329 stroke patients were investigated. Hemihyposthesia, hemianesthesia, hemineglect and homonymous hemianopsia were found in 37.4%, 13.8%, 7.9% and 7.3% respectively. MRDS was significantly higher in patients with hemianesthesia than other stroke patients, p<0.05. MRDS of patients with each of hemihypoestheisa, hemineglect and homonyous hemianopsia was not signigicantly different than patients without these abnormalities respectively. Patients with triad of hemianesthesia, hemineglect and homonymous hemianopsia had significantly higher MRDS than others , p<0.05. Conclusion: Hemianesthesia is the most important clinical effector on MRDS of the stroke patients. Presence of above triad predicts the highest MRDS in these patients.